HIGHER PEDAGOGICAL EDUCATION IN THE RUSSIAN FEDERATION: PROBLEMS OF TODAY AND WAYS TO IMPROVE QUALITY - S.V. Sapozhnikov (Academy of Cognitive and Natural Sciences, 2009)
The analysis of the problems of the higher pedagogical education in the Russian Federation as a country - member of the Black sea Economic Association in carried out in the article. Also the strategical orientators of the modernization of the modern schools providing general education are determined. The ways of the increasing of the quality of the pedagogical personnel preparation are outlined.